The strategies of students' morale strengthening at school (descriptive study at Cakranegara Mataram 4 Elementary School) - Sutisna, Deni; Indraswati, Dyah; Nursaptini, Nursaptini; Widodo, Arif; Anar, Ashar Pajarungi (Harmoni Sosial: Jurnal Pendidikan IPS, 2022)
This study examines the success of students' moral strengthening strategies through school culture. In examining the problem, this research uses a descriptive method. This research was conducted in Cakranegara Mataram 4 elementary school by studying and examining using observation method, interview, and documentation. Some of the findings obtained from the research show that the strategy of strengthening students' morale is implemented in some aspects: first on the vision and mission of the school where the school arranges the vision and mission and goals of the school which implies the value of faith, piety and religious, in order to strengthen student morale. Secondly, on activities, both activities within the school environment and activities outside the school environment relating to religious activities in order to increase religious value. The third is the application of teacher modeling which aims to provide good moral examples for students so the students can learn from existing models, that is, the teacher. Fourth, school facilities and infrastructure. Fifth, school rules are arranged based on the school's vision, mission, and goals. The results showed that the strategy successfully strengthened students' morale. However, there are still some obstacles found, such as the number of students who are not balanced with the number of classes and the number of less ideal teachers, the lack of maximum utilization of existing facilities, the lack of commitment of school residents, especially the lack of cooperation of parents in efforts to strengthen student morale.